KERAGAMAN GENETIK POPULASI Araucaria cunninghamii MENGGUNAKAN PENANDA RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - AYPBC Widyatmoko; Elisabeth Selda Patrisia Lejo; Aniek Prasetyaningsih; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
Genetic diversity was needed for supporting genetic conservation and tree improvement program. Araucaria cunnighamii is one of Indonesian conifer species which has various potential uses. Information about genetic diversity and its distribution, and genetic relationship can be revealed using RAPD (Random Amplified Polymorphic DNA) molecular marker. The objective of the study was to analyze genetic diversity within and among 8 populations of A. Cunninghamii, and genetic relationship between populations. Leaf samples of 64 trees were collected from 7 population in Papua and 1 population in Queensland (Australia). Genetic diversity was analyzed using 23 RAPD primers with 68 polymorphic loci. Mean genetic diversity within population was 0.270, and mean genetic distance among populations was 0.092. Some of the samples from the same population were grouped in the same cluster. But generally, the clustering of the samples. Genetic relationship among A. cunninghamii populations revealed that 8 populations were divided into two groups. First group was consisted of 7 population in Papua (Indonesia) and then split into 5 subcluster. Second group was population in Queensland (Australia).